A descriptive analysis of financial restatements in Malaysia / Ameen Qasem, Norhani Aripin and Wan Nordin Wan Hussin - Qasem, Ameen; Aripin, Norhani; Wan Hussin, Wan Nordin (Universiti Teknologi MARA Cawangan Sarawak, 2017)
This study provides an overview of the issue of financial restatements among Malaysian public listed companies by investigating the trend and reasons for financial restatements for the period beginning 2005 through to 2014. Based on the Thompson Reuters DataStream database which provides restatement data for 915 Malaysian companies (9,150 company-year observations), detailed analysis shows that there is a total of 1,945 (21.26%) restatements occurring during the period. The highest number of restatement occurrences was in 2010 with 342 cases (17.58%) while the lowest was in 2008 with 41 cases (2.11%). The majority of restatement cases occurred due to changes in accounting policies with more than 75% of financial restatement cases found within four sectors: industrial products, trading and services, consumer products, and technology. The results of the study will be useful to regulating bodies such as Bursa Malaysia, Securities Commission and Malaysian Accounting Standard Board in as much as they highlight the trend and reasons for financial restatements among Malaysian public listed companies. Further investigation could be conducted for companies that regularly change their accounting policies